Kontribusi Pendapatan Usahatani Padi Gogo terhadap Pendapatan Rumahtangga di Desa Lelekaa Kecamatan Wolasi Kabupaten Konawe Selatan - Nur, Farah Aulia; Taridala, Sitti Aida Adha; Sadimantara, Fahria Nadiryati (Department of Agribusiness, Halu Oleo University, 2020)
This research is motivated by the fact that Gogo Rice cultivated by the majority of the community in Lelekaa Village, Wolasi District, South Konawe has the main objective as the main source of food needs in the family. In addition to fulfilling food, Gogo rice is also a farm product that can be managed to increase farm household income. The purpose of this study was to determine how much Gogo rice farm income and its contribution to household income in the Lelekaa village. The location of the study was determined with the consideration that the majority of the people in Lelekaa Village were still consistently planting Gogo rice. The number of samples in this study was 29 people. The data analysis used is descriptive quantitative. There are two research results. First, the average income of upland rice farming in Lelekaa Village, Wolasi Subdistrict, Konawe Selatan Regency is Rp 4.769.144/MT in one year. Second, the contribution of Gogo rice farming income to household income in Lelekaa Village, Wolasi District, Konawe Selatan Regency was 17,92%. The contribution provided by other farms is smaller than Gogo rice farming with a percentage value of 9,28%, while the contribution of non-agricultural income to household income holds the greatest value with a percentage of 72,80%.